ESTABICAH: Relay of Cacah Numbers Games for Mathematics Skills in Early Elementary School - Andika, Windi Dwi; Berliani, Risma; Sumarni, Sri; Nusantara , Duano Sapta; Cahyani , Feby Indah; Soleha, Dwi Ardanti; Felisha , Melvi; Maharani (MIMBAR PGSD Undiksha, 2024)
The use of conventional methods, monotony, and lack of learning media results in students' lack of ability to understand the concept of numbers. The purpose of this study is to analyze the implementation of ESTABICAH games for early-grade elementary school students. This research uses a qualitative method involving students of elementary school. Data collection techniques in this study were carried out through the observation and documentation stages. Data analysis techniques are carried out in three stages, namely, data reduction, data presentation, and data verification. The results showed that ESTABICAH games made students interested in the process of learning mathematics. It was shown that 18 out of 20 students better understood the concept of numbers after participating in the ESTABICAH game. ESTABICAH game can support students' interest and enthusiasm in learning activities and make learning more fun so that students do not get bored when participating in mathematics learning. The ESTABICAH game can be applied as an alternative to help the process of learning mathematics in number skills, especially the concept of numbers.